Atmospheric circulation patterns which promote winter Arctic sea ice decline. (17th May 2017) - Luo, Binhe; Luo, Dehai; Wu, Lixin; Zhong, Linhao; Simmonds, Ian
Abstract: The impact of winter atmospheric blocking over the Ural Mountains region (UB) coincident with different phases of the North Atlantic Oscillation (NAO) on the sea ice variability over the Barents and Kara Seas (BKS) in winter is investigated. It is found that the UB in conjunction with the positive phase of the NAO (NAO + ) leads to the strongest sea ice decline. During this phase composites and trajectory analyses reveal an efficient moisture pathway to the BKS from the mid-latitude North Atlantic near the Gulf Stream Extension region where water vapor is abundant due to high sea surface temperatures. The NAO + -UB combination is an optimal circulation pattern that significantly increases the BKS water vapor that plays a major role in the BKS warming and sea ice reduction, while the increased sensible and latent heat fluxes play secondary roles. By contrast, much fewer dramatic impacts on the BKS are observed when the UB coincides with the neutral or negative phases of the NAO. Our results present new insights into the complex processes involved with Arctic sea ice reduction and warming. The mechanisms highlighted here potentially offer a perspective into the mechanisms behind Arctic multi-decadal climate variability.